Development of a Training Package in School Mathematics (DTPSM) for Pre-Service and In-Service Teachers - Vijayalakshmi, Prof. Ch.; Shailaja, Mrs. K. V. (INDIAN EDUCATIONAL REVIEW, 2012)
The country needs, today effective and productive citizens who display scientific and constructive thinking and attitudes in all walks of life. In this direction, a new chapter is opined into the 21st century, which is going to be an era of science and technology. The child of today has to be prepared for this era of technology for which a strong base of mathematics education is a necessity. Mathematics has prominent place at the school. Secondary education is the minimum requirement for life. After completing Secondary education some students enters into life while others go in for higher education. It is on account of this fact, that it has been suggested that the curriculum at the secondary stage should be terminus as well as preparatory and should comprise mathematics.